The Role of Affect in Understanding Leaders’ Influence on Followers and How Followers Can Influence Leaders - Rashid, Muhammad Salman (Auckland University of Technology, 2022)
Leadership is one important element that organizations enact to garner effective behaviors and superior performance from employees. Researchers continuously look for the ways through which leaders can influence their followers. During the last couple of decades, much research has focused on the role of leaders' affect (e.g., experience and expression of moods and emotions) in influencing followers' work outcomes. However, the complexities of leadership affective influences, which is likely to involve multiple underlying mechanisms and contextual factors facilitating (hindering) leader-follower affect transfer, are not well understood. Since followers play an essential role in the creation and operations of leadership, there are theoretical possibilities of followers' affective influences on leaders, but empirical evidence is scant. This thesis aims to explore the role of leadership and followership affective influences through the affective and cognitive mechanisms on various outcome variables. This is a thesis by manuscripts and is based on one review paper (Chapter 4) and four empirical papers (Chapter 5-8). Therefore, the majority of the chapters, although related, are standalone papers. These papers are under review or final manuscripts submitted to targeted journals, as indicated at the start of each chapter. Chapters 1 and 2 provide the rationale, detailed literature review of leadership and affect research and related theoretical approaches to explain relationships. From this review, broad research questions are developed that bind all papers of the thesis. Chapter 3 briefly describe the methodology of the five separate papers. Paper 1 (Chapter 4), a mapping review based on review and theoretical articles dated 2005-2020, provides an integrative review of leadership and affect theory and evidence, resulting in the identification of four running themes: leaders' affect and followers' outcomes, leadership and emotional labor, affective influences of non-affective leadership, and affect reciprocity and follower affective influences. This review then proposes two general frameworks that can help shape future research on the role of affect in leadership and followership. Paper 1 also outlined the improved methodologies to examine the phenomena of affect in field studies along with looking at leadership/followership affective influences through the lens of emotions as social information theory (EASI: Van Kleef, 2009). Building on Paper 1, leadership affective influences on followers are explored in Paper 2-4 (Chapter 5-7), and followers' affective influences in Paper 5 (Chapter 8) using the EASI theory as a theoretical lens to understand the relationships. Paper 2 focus on how leader positive and negative affect influence followers' affective experiences and organizational citizenship behaviors (OCBs) using time-lagged data of a leader-follower sample. Paper 3 explored the influence of leader surface and deep acting (e.g., leader emotional labor) on followers' work engagement using time-lagged data of a leaders-followers sample. Paper 3 focus on combining affective and non-affective behaviors of leaders (e.g., leadership interpersonal justice) and examine the influence on followers' job satisfaction using daily diary data across five days. Theoretically, these papers (Paper 2-4, Chapter 5-7) tested the underlying mechanisms of leader to followers affective influences, which are further contingent on individual and situational factors. Overall, findings support the beneficial effects of leader positive affective display, using deep acting and doing interpersonal justice. Interestingly, some results indicate the potential effectiveness of leader negative affect (e.g., performance-related worries/sadness) for followers, but only under certain contextual factors such as when followers' have high emotional intelligence and leaders' have a high tendency to express genuine emotions. Paper 5 (Chapter 8) explored how followers' positive and negative affect can influence leaders' support behaviors through affective and cognitive reactions of leaders using a two-sample design and time-lagged data. Results support the direct influence of followers' affect on leaders and partial support for indirect impacts. Throughout the empirical papers, mediation and moderations effects were tested and supported. In general, the findings of this thesis revealed that it is essential to consider multiple facets of leadership affective influences (e.g., positive and negative affective display, emotional labor, and affective influences of non-affective behaviors). Notably, all of these facets of leadership affective influences are not straightforward, but operates through affective and cognitive processes, and can be contingent on the individual (leader and follower) and contextual factors of the leader-follower relationship. Similarly, follower affective influences can travel through direct and indirect pathways to influence leaders, and this influence is also contingent on context. Overall, this thesis contributes to the leadership and affect literature by providing an integrative review and identifying research gaps, which are then empirically tested. Findings based on diverse samples, predominantly from Pakistan, using various methodologies including daily diary and time-lagged multilevel designs, provide robust evidence around the leadership and followership affective influences. Under EASI theory, this thesis contributes to understanding around the precise underlying mechanisms and contextual factors that facilitate leader-to-follower affective influences, and also shed light on the rarely explored upward affective influences from followers to leaders. These findings have solid theoretical implications, including testing much of the EASI theory assertions around the parallel presence of affective and inferential processes in interpersonal affect transmission, and managerial implications around the realization of affect-based influences in leadership and followership process and outcomes.
Keywords: Leadership; Followership; Interpersonal Affect Transfer; Daily Affective Influences; Cognitive and Affective Pathways; Genuine and Regulated Affect; Multilevel Design; Experience Sampling; EASI Theory; Pakistan and New Zealand